CD44 targeted delivery of oncolytic Newcastle disease virus encapsulated in thiolated chitosan for sustained release in cervical cancer: a targeted immunotherapy approach - Kousar, Kousain; Naseer, Faiza; Abduh, Maisa Siddiq; Anjum, Sadia; Ahmad, Tahir (Frontiers in Immunology, 2023)
Introduction Cervical cancer accounts for one of most common cancers among women of reproductive age. Oncolytic virotherapy has emerged as a promising immunotherapy modality but it comes with several drawbacks that include rapid clearance of virus from body due to immune-neutralization of virus in host. To overcome this, we encapsulated oncolytic Newcastle disease virus (NDV) in polymeric thiolated chitosan nanoparticles. For active targeting of virus loaded nanoformulation against CD44 (cluster of differentiation 44) receptors which are overly expressed on cancer cells, these nanoparticles were surface functionalized with hyaluronic acid (HA). Methods Using half dose of NDV (TCID50 (50% tissue culture infective dose) single dose 3 × 105), virus loaded nanoparticles were prepared by green synthesis approach through ionotropic gelation method. Zeta analysis was performed to analyse size and charge on nanoparticles. Nanoparticles (NPs) shape and size were analysed by SEM (scanning electron microscope) and TEM (transmission electron microscope) while functional group identification was done by FTIR (fourier transform infrared) and XRD (X-ray diffraction). Viral quantification was done by TCID50 and Multiplicity of infection (MOI) determination while oncolytic potential of NPs encapsulated virus was analysed by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay and cell morphology analysis. Results Zeta analysis showed that average size of NDV loaded thiolated chitosan nanoparticles surface functionalized with HA (HA-ThCs-NDV) was 290.4nm with zeta potential of 22.3 mV and 0.265 PDI (polydispersity index). SEM and TEM analysis showed smooth surface and spherical features of nanoparticles. FTIR and XRD confirmed the presence of characteristic functional groups and successful encapsulation of the virus. In vitro release showed continuous but sustained release of NDV for up to 48 hours. TCID50 for HA-ThCs-NDV nanoparticles was 2.63x 106/mL titter and the nanoformulation exhibited high oncolytic potential in cell morphology analysis and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay as compared to naked virus, in dose dependent manner. Discussion These findings suggest that virus encapsulation in thiolated chitosan nanoparticles and surface functionalization with HA is not only helpful in achieving active targeting while masking virus from immune system but, it also gives sustained release of virus in tumor microenvironment for longer period of time that increases bioavailability of virus.